2021
DOI: 10.1186/s12909-021-02821-6
|View full text |Cite
|
Sign up to set email alerts
|

Peer review in team-based learning: influencing feedback literacy

Abstract: Background Peer review in Team-based learning (TBL) exists for three key reasons: to promote reflection on individual behaviours; provide opportunities to develop professional skills; and prevent ‘free riders’ who fail to contribute effectively to team discussions. A well-developed process that engages students is needed. However, evidence suggests it remains a difficult task to effectively incorporate into TBL. The purpose of this study was to assess medical students’ ability to provide writte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 30 publications
(33 reference statements)
2
15
0
2
Order By: Relevance
“…TBL is a student-centered, research-based instructional practice (RBIP) that has been implemented in a variety of courses, disciplines, and contexts, but few of the published accounts of TBL describe online implementation. The extensive research on TBL in F2F contexts aided in identifying the critical components of the approach, which, in turn, made it easier to identify ways to adapt TBL for the online environment without sacrificing fidelity.…”
Section: Discussionmentioning
confidence: 99%
“…TBL is a student-centered, research-based instructional practice (RBIP) that has been implemented in a variety of courses, disciplines, and contexts, but few of the published accounts of TBL describe online implementation. The extensive research on TBL in F2F contexts aided in identifying the critical components of the approach, which, in turn, made it easier to identify ways to adapt TBL for the online environment without sacrificing fidelity.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on peer review using a specific rubric to assess the quality of medical student peer feedback during a team exercise highlighted the need for training in this area. Common breaches in professional feedback included ‘cutting and pasting’, as well as banal feedback [ 28 ]. This study found that while students were comfortable identifying positive learning behaviours of their peers, they were less able to identify needs for improvement (gap) and detail a plan for improvement (action) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Common breaches in professional feedback included ‘cutting and pasting’, as well as banal feedback [ 28 ]. This study found that while students were comfortable identifying positive learning behaviours of their peers, they were less able to identify needs for improvement (gap) and detail a plan for improvement (action) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The real challenge lies in two non-structural, albeit structurally contingent, goals: achieving a real improvement process with all teams and, with it, make the TBL strategy an efficient passage for the mastery of course contents by all students. Student accountability is argued as a very important means to achieve this (Michaelsen & Sweet, 2008a, 2008b, 2011Michaelsen, 1992;Burgess et al, 2021), hence the worthiness of peer evaluation in succeeding with TBL.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the exam results did not reflect a stimulus to performance by the TBL sessions: in 2016 the students did not invest their time in preparing for the exam, and in 2017 and 2018 only a minority completed the continuous assessment option. Peer evaluation is instrumental in making students individually accountable within the TBL strategy (Michaelsen & Sweet, 2008a, 2008b, 2011Michaelsen, 1992;Burgess et al 2021) and is not properly replaced by complementary evaluations. Thus, it is an essential part of a skillful fashioning of team composition to scatter students that are judged likely to become absentees in order to minimize the possibility of some teams being hurt by such behavior more than others.…”
Section: The Adaptationsmentioning
confidence: 99%